Global cross-sectional survey of women with vasomotor symptoms associated with menopause: prevalence and quality of life burden. Issue 8 (August 2021) - Nappi, Rossella E.; Kroll, Robin; Siddiqui, Emad; Stoykova, Boyka; Rea, Carol; Gemmen, Eric; Schultz, Neil M.
Abstract: Objective: To determine prevalence and health-related quality of life (HRQOL) of moderate-to-severe vasomotor symptoms (VMS) in postmenopausal women in Europe, the US, and Japan, and among subgroups of women not taking hormone therapy (HT). Methods: Screening surveys were sent to a random sample of women aged 40 to 65 years; full questionnaires followed to those who completed them and met inclusion criteria. Women with successfully treated VMS, breast cancer, or on HT for medical conditions were excluded. The Menopause-Specific QOL (MENQOL) and Work Productivity and Activity Impairment (WPAI) questionnaires were included in the questionnaire. Results: Of 25, 161 women completing the screening survey, 11, 771 were postmenopausal and 3, 460 met inclusion criteria and completed the full questionnaire. Prevalence of moderate-to-severe VMS was 40%, 34%, and 16% in Europe, the US, and Japan, respectively. A large proportion were HT averse, albeit eligible (Europe 56%, US 54%, Japan 79%). In total, 12%, 9%, and 8% in Europe, the US, and Japan, respectively, were HT-contraindicated. A high proportion were HT-cautious (Europe 70%, US 69%, Japan 52%). Most common menopausal symptoms reported in the MENQOL were feeling tired or worn out (Europe/US 74%, Japan 75%), aching in muscles and joints (Europe 69%, US 68%, Japan 61%), difficulty sleeping (Europe 69%, US 66%, Japan 60%), and hot flashes (Europe 67%, US 68%, Japan 62%). Overall, the most bothersome symptom was weight gain. As measured by the WPAI, hot flashes and night sweats had a greater impact on daily activities than on working activities. Conclusions: A high proportion of women experienced moderate-to-severe VMS, with associated symptoms impacting QOL. Abstract : Supplemental Digital Content is available in the text